KEEFEKTIFAN AUGMENTED REALITY TERHADAP HASIL BELAJAR IPA KELAS V SDN BARURAMBAT KOTA 01 PAMEKASAN - Weny Eka Yulia Fajrin; Nadya Ayu Faradila; Anisa Nurhikmah; Yoga Dwi Saputra; Urvia Zahna Rohandy; Fiki Riehaz Zuhdi; Faizol; Ika Dian Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of Augmented Reality (AR)-based instructional media in enhancing students' understanding of science, particularly on the topic of the respiratory system, among fifth-grade students at State Elementary School Barurambat Kota 1 Pamekasan. The research was motivated by students' difficulties in grasping the structure and function of respiratory organs due to the limitations of conventional two-dimensional learning media. The study employed a pre-experimental design using a one-group pretest-posttest model. The sample consisted of 25 students. A validated multiple-choice test was used as the research instrument. Data analysis involved the use of N-Gain calculations and a paired sample t-test with the assistance of SPSS software.The results indicated an average N-Gain score of 0.3337, which falls into the moderate category, suggesting a measurable improvement in students’ learning outcomes following the implementation of AR media. Furthermore, the paired t-test revealed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between pretest and posttest scores. The students' average score increased from 58.40 to 75.00 after the intervention. These findings suggest that AR-based learning media positively contribute to conceptual understanding by offering interactive 3D visualizations, making the learning process more engaging and meaningful. This aligns with the principles of 21st-century learning, which emphasize student-centered approaches and the integration of technology to foster contextual and immersive learning experiences